An exploration into the ZKP software space - Van Niekerk, Nadia (Stellenbosch : Stellenbosch University, 2025)
van Niekerk, N. 2025. An Exploration into the ZKP Software Space. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/b99e335e-2eb7-4094-b668-096bac91d3a0